Avaliação comparativa de metodologias para análise de dióxido de cloro - Santos, Ítalo Lima dos (2011)
Considering that in Brazil the use of chlorine dioxide in water treatment is still not adopted due to both its high cost and difficulty of its quantification, we intend to compare three methods used to quantify this product. We chose the methodology LGB (not referenced) and compared with the EPA method 327.0 (Environmental Protection Agency () and amperometric titration (referenced), both analyzed under the same dilution. With that in mind, we aim to also compare the effects of varying the dilution specifically the methodology amperometric titration. for the analysis methodology, we use the F test to determine the accuracy, the test point hypothesis, to determine the accuracy of the methodologies and the possible existence of a tendency among them, the t test to analyze the existence of systematic errors among methods, the one-way ANOVA test to analyze the effects of dilution in the amperometric titration. The comparison allowed us to conclude that the methodology did not provide LGB variance of repeatability and intermediate precision worse than the one presented in the methodology EPA method 327.0 and the amperometric titration level of 95%, despite the dispersion from the mean and median.